(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Crowd funding is a digital financing model through which individuals, entrepreneurs, or businesses secure funds from a large number of contributors, typically via the Internet. This method leverages online platforms to gather small financial contributions from a broad audience, collectively referred to as "the crowd," rather than soliciting substantial amounts from a limited number of traditional investors such as banks or venture capitalists. Crowd funding has gained significant traction across various sectors, including the arts, entrepreneurship, and scientific research, owing to its accessibility and community-oriented nature. One of the primary advantages of crowd funding is its capacity to democratize financial access. It offers opportunities for a diverse range of participants, including novice creators and small-scale entrepreneurs, to present their ideas and obtain support without substantial capital or recognition. Crowd funding manifests in various forms, each tailored to distinct needs. Reward-based crowd funding involves supporters receiving non-financial incentives for their contributions, which may include items such as thank-you notes or product prototypes. Equity crowd funding allows backers to acquire shares in a company, thereby securing financial interest in its success. Donation-based crowd funding relies on voluntary contributions, often employed for charitable purposes, without the expectation of monetary return. Finally, peer-to-peer lending facilitates loans between individuals and small businesses, offering lenders potential returns through interest. Crowd funding has transformed the financial support landscape for projects by offering an inclusive, accessible, and adaptable model that promotes innovation and community involvement. Despite challenges, such as the dissemination of crowd funding, variations in success rates, and potential biases, the model continues to develop and expand, providing new opportunities for artists, innovators, and change-makers.1 Crowd funding represents one dimension of the phenomenon of crowd sourcing besides crowd voting and crowd creation. The term crowd sourcing is composed of "crowd" and "outsourcing", pointing to the meaning to outsource specific functions to a group of external persons. The concept is based on the idea of "wisdom of a crowd". The act of taking a job traditionally performed by a designated agent (usually an employee) and outsourcing it to an undefined, generally large of people in the form of an open call. Besides crowd sourcing, crowd funding is closely connected to micro lending. Micro lending refers to the idea of funding of individuals, who do not have access to conventional financing from credit institutions.